Towards Strategic Planning Implementation for Egyptian Cities - Marwa Ahmed Soliman (Environmental Science and Sustainable Development, 2018)
Strategic urban planning plays a real and significant role in developing the urban areas worldwide because it helps in mitigating the loss of lands; especially in diversion of urban growth away from the “agricultural lands”. It provides better urban services and utilities; in terms of quality; and enhances local economy, livability, and sustainability. This paper explores the importance of strategic plans and their role in sustainable development, in addition to exploring the importance of the implementation process. A questionnaire with the local authorities for a group of 19 cities was implemented. The case studies for the planning of such cities started more than 4 years ago. It has been found that there are many implementation problems that prevent the conversion process. The aim of this paper is represented in two main points. Firstly, illustrating the concept of the strategic planning process and how Egypt deals with it. Secondly, suggesting a new implementation system which can solve the main implementation problems in Egypt. In conclusion, the paper identifies, through statistics, the perspectives of local government staff in Egypt towards the preparation and implementation of the strategic plans which includes proposed solutions for a problem treatment as well as the opportunity of community participation.